Extending cBioPortal for Therapy Recommendation Documentation in Molecular Tumor Boards: Development and Usability Study - Renner, Christopher; Reimer, Niklas; Christoph, Jan; Busch, Hauke; Metzger, Patrick; Boerries, Melanie; Ustjanzew, Arsenij; Boehm, Dominik; Unberath, Philipp (JMIR Medical Informatics, 2023)
Background: In molecular tumor boards (MTBs), patients with rare or advanced cancers are discussed by a multidisciplinary team of health care professionals. Software support for MTBs is lacking; in particular, tools for preparing and documenting MTB therapy recommendations need to be developed. Objective: We aimed to implement an extension to cBioPortal to provide a tool for the documentation of therapy recommendations from MTB sessions in a secure and standardized manner. The developed extension should be embedded in the patient view of cBioPortal to enable easy documentation during MTB sessions. The resulting architecture for storing therapy recommendations should be integrable into various hospital information systems. Methods: On the basis of a requirements analysis and technology analysis for authentication techniques, a prototype was developed and iteratively refined through a user-centered development process. In conclusion, the tool was evaluated via a usability evaluation, including interviews, structured questionnaires, and the System Usability Scale. Results: The patient view of cBioPortal was extended with a new tab that enables users to document MTB sessions and therapy recommendations. The role-based access control was expanded to allow for a finer distinction among the rights to view, edit, and delete data. The usability evaluation showed overall good usability and a System Usability Scale score of 83.57. Conclusions: This study demonstrates how cBioPortal can be extended to not only visualize MTB patient data but also be used as a documentation platform for therapy recommendations.
CRIS-Team Scopus Importer:2024-12-16
Keywords: cancer; cBioPortal; development; documentation platform; genomics; health information interoperability; implementation; molecular tumor board; platform; precision; precision medicine; tool; tumor; usability evaluation; use; user-centered